Application and Prospects of Artificial Intelligence in Breast Cancer Early Diagnosis, Screening, and Treatment - Yu, Dian (Transactions on Materials, Biotechnology and Life Sciences, 2024)
In modern society, as artificial intelligence technology becomes increasingly mature, AI can already be utilized to assess and treat breast carcinoma. By summarizing results and data of experiments that use AI to help breast carcinoma diagnosis and cure, this article states the positive impact of AI on breast cancer screening, detection of breast cancer-related genes, and prediction of efficacy of breast cancer treatment drugs. What is more, illustrating the moral, legal, and social challenges encountered by scientists when they use artificial intelligence. Also, this article makes some suggestions for the future development of AI technology. The author believes that AI technology have the ability to contribute significantly to the diagnosis and cure of breast cancer and can enhance the chances of patients surviving to a considerable extent. However, currently, artificial intelligence technology remains in a relatively nascent stage, necessitating ongoing attention and dedicated efforts for its advancement.